Bordetella pertussis - Fouch, Sarah (Henry Stewart Talks, 2025)
Bordetella morphology, Clinical conditions including phases and symptoms, Catarrhal, Paroxysmal and Convalescent phase of whooping cough, Virulence factors, Secreted toxins